2019
DOI: 10.1002/oby.22476
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Predictors of Weight Regain at 1‐Year Follow‐Up in Weight‐Reduced Adults with Obesity

Abstract: Objective This study aimed to assess whether changes in resting metabolic rate (RMR), exercise‐induced energy expenditure (EIEE), and appetite following weight loss (WL) are associated with weight regain at 1 year. Methods Thirty‐six adults with obesity underwent 8 weeks of a very‐low‐energy diet, followed by 4 weeks of refeeding and a 1‐year maintenance program. RMR, EIEE, appetite ratings, and active ghrelin, peptide YY, glucagon‐like peptide‐1, cholecystokinin, and insulin concentrations were measured at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
1
16
2
Order By: Relevance
“…Three models have been proposed to explain this phenomenon (15), but whilst energy expenditure adaptations may influence maintenance success, it is changes in appetite regulation that are considered the main driver of weight regain (16). The extent to which these mechanisms are causal remains largely speculative since evidence linking both hormonal (11,(17)(18)(19) and energy expenditure (20) adaptations with weight regain is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Three models have been proposed to explain this phenomenon (15), but whilst energy expenditure adaptations may influence maintenance success, it is changes in appetite regulation that are considered the main driver of weight regain (16). The extent to which these mechanisms are causal remains largely speculative since evidence linking both hormonal (11,(17)(18)(19) and energy expenditure (20) adaptations with weight regain is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Vogels et al (5) reported weight regain at 2 years of follow‐up to correlate negatively with baseline (pre‐WL) RMR in 91 individuals with overweight and obesity who had initially lost an average of 8 kg through a very‐low‐energy diet. However, in a recently published study from our group, in a mixed sample of men and women who were not examined in energy balance, baseline (pre‐WL) RMR or RQ was not correlated with weight regain at 1 year of follow‐up after an initial 17% WL induced by a very‐low‐energy diet (24). It is interesting to see that these findings were reproduced in the present analysis in a very different study population of premenopausal women with family history of overweight/obesity who were assessed under energy balance conditions.…”
Section: Discussionmentioning
confidence: 76%
“…Pasman et al (26), moreover, reported that the amount of weight regained at 14‐month follow‐up in premenopausal women with obesity was larger in those who experienced the greatest decrease in RMR and physical activity energy expenditure (measured with an activity monitor) in response to a 2‐month low‐energy diet. We have recently shown that the reduction in RMR observed with a 17% WL (followed by 4 weeks of weight stabilization) was not predictive of weight regain at 1‐year follow‐up (24). The search for accurate and clinically relevant baseline predictors of weight regain remains, therefore, a pressing area of research.…”
Section: Discussionmentioning
confidence: 99%
“…Pasman et al ( 61 ), on the other hand, reported that the amount of weight regained at 14 months of follow-up in premenopausal women with obesity was larger in those who experienced the greatest decrease in measured RMR and physical activity EE (measured with an activity monitor) in response to a 2-month low-energy diet. We have recently shown that the reductions in RMR and exercise-induced EE that are observed with a 17% WL (followed by 4 weeks of weight stabilization) were not predictive of weight regain at a 1-year follow-up ( 62 ). Moreover, as previously discussed, even the studies showing metabolic adaptation fail to report an association between this phenomenon and weight regain ( 26 , 27 ).…”
Section: Compensatory Responses To Weight Lossmentioning
confidence: 99%
“…Adding to this, Strohacker and colleagues ( 69 ) found no evidence in their 2014 review that the increase in ghrelin secretion observed with WL was associated with weight regain. We have also recently published evidence that the increased hunger feelings in fasting ( r = -0.099; P = 0.564; n = 36) and basal and postprandial ghrelin secretion [ r = -0.328 ( P = 0.058) and r = -0.333 ( P = 0.055), respectively; n = 36] seen with diet-induced WL (20 kg, 17%) are not associated with weight regain at 1 year of follow-up in a group of individuals with obesity at baseline (BMI = 36.6 ± 4.3 kg/m 2 ) ( 70 ). A recently published study by Thom and colleagues ( 63 ) showed again no association between the increase in basal plasma ghrelin concentration at 6 months after diet-induced WL (14 kg, 14%) and weight regain between 6 and 24 months of follow-up (no correlation coefficient or significance level provided) in a group of individuals with obesity (BMI = 39.4 ± 4.3 kg/m 2 ).…”
Section: Compensatory Responses To Weight Lossmentioning
confidence: 99%